The Potential of ordinary compost and vermicompost bacterial isolates in reducing the harmful bloom of microcystis aeruginosa - Ramos, Maria Shiela K.
Freshwater resources including estuaries are threatened by the presence and inncrease incidence of harmful algal blooms (HAB)worldwide especially those where Microcystis aeruginosa is the most dominant cyanobacterial species. The HABs are oftentimes a direct result of antrophogenic pollution entering water bodies, such as partially treated and even raw nutrient-rich effluents and the leaching of fertilizers and animal wastes. The impact of HABs on aquatic ecosystems and water resources, as well as their human health implications are well documented. Countermeasures have been proposed and implemented to manage HABs with varying levels of success.